Fractured solidarities: labour regulation, workplace restructuring, and employment 'flexibility' in Namibia - Klerck, Gilton (Rhodes University, Faculty of Humanities, Department of Sociology and Industrial Sociology, 2005)
A central concern of this thesis is the expansion, distribution and control of 'non-standard' employment in Namibia since independence. The employment relationship has assumed various historical forms under capitalism, each of which corresponds to a specific mode of regulation with distinct structural dynamics. An attempt is made to extend the regulation approach 'downwards' to account for the problem of order in the workplace and to place the employment relationship within its own regulatory framework. The point of departure in this study of the dynamics of labour regulation is the contradictory nature of labour's incorporation, allocation, control and reproduction within the labour market. The employment relationship is never only an economic exchange, but is also mediated through an institutional framework that connects the processes of production and social reproduction, and regulates conflicting interests inside and outside the workplace. This relationship, as critical realists have pointed out, is a product of the indeterminate intersection of several generative structures. The roots of these generative structures can be traced to three sets of social processes: the processes of production and the structuring of labour demand; the processes of social reproduction and the structuring of labour supply; and the forces of regulation. Non-standard employment is viewed as a particular social and spatio-temporal 'fix' for the various regulatory dilemmas generated by the standard employment relationship. This conception underscores the fact that a national system of labour regulation decisively shapes the conditions under which employers are able to casualise a part of their workforce. The differential experience across national boundaries suggests that analytical space needs to be provided for systems of labour market regulation which may either accentuate or moderate pressures for casualisation. Segmentation on the demand side of the labour market is explored through an analysis of the types of non-standard jobs created in different economic sectors. The various forms of employment 'flexibility' tend to vary in importance according to the specific manner in which a firm chooses to compete. Consequently, non-standard employees are distributed in a complex and uneven manner across industrial sectors and the occupational hierarchy, and face a diverse range of possibilities and liabilities that shape their levels and forms of participation in the labour market. By counteracting the homogenisation effects of labour law and collective bargaining, the mobilisation of cheap and disposable labour through non-standard employment contracts allows employers much greater discretion in constructing the wage-effort bargain. With non-standard employment, social and statutory regulation is weak or underdeveloped and hence managerial control is autocratic, with a significant contractual component. Although the changing social composition of the workforce associated with employment 'flexibility' poses serious challenges to the modes of organisation that have long served the labour movement, trade unions in Namibia and elsewhere have been slow to respond to the threats of casualisation. Of concern here, is the extent to which attempts to promote the security of existing union members is compatible with attempts to organise non-standard employees. This thesis shows that the unions have developed a complex amalgam of strategies in their efforts to regulate non-standard employment relationships.
Keywords: Industrial relations -- Namibia; Labor -- Namibia; Labor unions -- Namibia; Organizational change -- Namibia; Labor laws and legislation -- Namibia; Casual labor -- Namibia